External Environmental Factors and the Development of Oil Palm in Edo State Nigeria - A. , BY OGUH Festus; Friday, ADJENE (Research Parks Publishers, 2023)
The study examined the influence of external environmental factors on oil palm development in Edo state, located in South-South region of Nigeria. The growth of oil palm sub sector of crop farming in Agricultural industry has been greatly influenced by some environmental factors over the years. Therefore, this study has investigated the role played in either undermining the growth and development of oil palm or improving its performance. A literature review of related works along with the use of structured questionnaire was used to source primary data which were analysed to analysed the data in other to test the formulated hypothesis. A population of 184 oil palm farms across Edo State was used and the Taro Yamane method was used to determine the sample size. The questionnaire and responses were designed using the five Likert scales The hypothesis was tested using the chi-square method. The result of the analysis revealed that external environmental factors had negatively influenced the oil palm development in Edo state. Prevalent challenges identified by the study included funding, government intervention and insecurity. It was recommended that government should do a lot more to improve on the method of oil palm production s many farms were operated on a subsistence method. This will go a long way in improving oil palm production in Edo state to make it commercially viable